The moderating role of social competence in the association between adolescent mental health symptomatology and substance use - Boyd, Ciara E., author; Riggs, Nathaniel, advisor; Haddock, Shelley, committee member; Brown, Sami, committee member (Colorado State University. Libraries, 2022)
During adolescence, substance misuse and mental health problems often co-occur, yet there have been few studies testing for whom the association between mental health and substance use is the strongest. The purpose of this study was to gain a comprehensive understanding of the moderating role of social competence on the association between adolescent anxiety and depression symptomology and nicotine and cannabis use. This study used data from 3,383 ninth grade students who participated in the University of Southern California Health and Happiness study. Participants completed a self-report survey during the fall semester of the ninth grade. Main effects and moderating associations were tested using hierarchical multiple regression analyses. Results demonstrated significant associations between depressive symptomatology and lifetime nicotine and cannabis use, however, no significant associations were found between substance use and anxiety. Social competence as an independent variable was associated with cannabis and nicotine use, yet interaction terms were not associated with substance use. Results from this study suggest that both depression and social competence are uniquely associated with lifetime nicotine and cannabis use in adolescence. Therefore, substance use treatment programs should focus on both decreasing depression and increasing social competence. Future studies should test these associations beyond ninth graders in one large metropolitan area in the United States.